Efficacy of convalescent plasma for treatment of COVID-19 in Uganda. Issue 1 (9th August 2021) - Kirenga, Bruce; Byakika-Kibwika, Pauline; Muttamba, Winters; Kayongo, Alex; Loryndah, Namakula Olive; Mugenyi, Levicatus; Kiwanuka, Noah; Lusiba, John; Atukunda, Angella; Mugume, Raymond; Ssali, Francis; Ddungu, Henry; et al.
Abstract : Rationale: Convalescent plasma (CCP) has been studied as a potential therapy for COVID-19, but data on its efficacy in Africa are limited. Objective: In this trial we set out to determine the efficacy of CCP for treatment of COVID-19 in Uganda. Measurements: Patients with a positive SARS-CoV-2 reverse transcriptase (RT)-PCR test irrespective of disease severity were hospitalised and randomised to receive either COVID-19 CCP plus standard of care (SOC) or SOC alone. The primary outcome was time to viral clearance, defined as having two consecutive RT-PCR-negative tests by day 28. Secondary outcomes included time to symptom resolution, clinical status on the modified WHO Ordinal Clinical Scale (≥1-point increase), progression to severe/critical condition (defined as oxygen saturation <93% or needing oxygen), mortality and safety. Main results: A total of 136 patients were randomised, 69 to CCP+SOC and 67 to SOC only. The median age was 50 years (IQR: 38.5–62.0), 71.3% were male and the median duration of symptom was 7 days (IQR=4–8). Time to viral clearance was not different between the CCP+SOC and SOC arms (median of 6 days (IQR=4–11) vs 4 (IQR=4–6), p=0.196). There were no statistically significant differences in secondary outcomes in CCP+SOC versus SOC: time to symptom resolution (median=7 (IQR=5–7) vs 7 (IQR=5–10) days, p=0.450), disease progression (9 (22.0%) vs 7 (24.0%) patients, p=0.830) and mortality (10 (14.5%) vs 8 (11.9%) deaths, p=0.476). Conclusion: In this African trial, CCP therapy did not result in beneficial virological or clinical improvements. Further trials are needed to determine subgroups of patients who may benefit from CCP in Africa. Trial registration number NCT04542941 .